(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article explores the core concepts of communicative competence in language teaching. It delves into the historical development of the term, highlighting the contributions of key scholars like Chomsky and Hymes. The article then unpacks the various components of communicative competence, including grammatical knowledge, sociolinguistic awareness, and strategic competence. Finally, it discusses the implications of this framework for designing effective language learning activities